Research of thermoelectric null-thermostat - O. V. Evdulov; D. A. Magomedov; R. M. Magomedov; K. A. Shikhabidov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The purpose of the study is to develop and study the design of a thermoelectric null-thermostat, characterized by low power consumption, in which high accuracy of temperature stabilization of the reference junctions of differential thermocouples is achieved by placing them directly near the water-ice interface.Method. The study was carried out on an experimental model of a thermoelectric null-thermostat. To study heat transfer processes, visual observation of the movement of the ice-water interface in the null-thermostat chamber was carried out. Temperature values were recorded at the lower and upper bases of the chamber, as well as at the hot and cold junctions of the thermoelectric module (TEM) using thermocouples.Result. The dependences of the change in temperature of the upper and lower base of the working chamber, as well as the phase boundary over time, the duration of time for complete ice penetration on the TEM supply current, and the temperature difference, respectively, between the surface of the cold junction of the TEM and the lower base of the working chamber were obtained , the surface of the hot junction of the thermal module and the upper base of the working chamber.Conclusion. It has been established that the speed of movement of the phase boundary strongly depends on the value of the supply current of the thermoelectric battery, which corresponds to the heat flow at the upper and lower base of the working chamber. As follows from the data presented, the change in temperature of the upper base is more noticeable than the lower one. At a current of 2, 4 and 6 A, the speed of movement of the phase boundary is 0.007 m/h, 0.01 m/h and 0.013 m/h, respectively. In this case, the duration of complete melting of ice, corresponding to the duration of operation of the null thermostat, when the TEM supply current changes from 2 to 7 A, is reduced from 1,91⋅104 s to 1,38⋅104.